PH-responsive gold nanoclusters-based nanoprobes for lung cancer targeted near-infrared fluorescence imaging and chemo-photodynamic therapy. (1st March 2018) - Xia, Fangfang; Hou, Wenxiu; Zhang, Chunlei; Zhi, Xiao; Cheng, Jin; de la Fuente, Jesús M.; Song, Jie; Cui, Daxiang
Graphical abstract: Abstract: Nanoparticle-based drug delivery systems have drawn a great deal of attention for their opportunities to improve cancer treatments over intrinsic limits of conventional cancer therapies. Herein, we developed the polypeptide-modified gold nanoclusters (GNCs)-based nanoprobes for tumor-targeted near-infrared fluorescence imaging and chemo-photodynamic therapy. The nanoprobes comprise of tetra-functional components: i) polyethylene glycol (PEG) shell for long blood circulation and better biocompatibility; ii) MMP2 polypeptide (CPLGVRGRGDS) for tumor targeting; iii) cis -aconitic anhydride-modified doxorubicin (CAD) for pH-sensitive drug release; iv) photosensitizer chlorin e6 (Ce6) for photodynamic therapy and fluorescence imaging. The in vitro results demonstrated that the as-synthesized nanoprobes could be efficiently internalized into A549 cells and then significantly enhance the mortality of cancer cells compared with free Ce6 and doxorubicin. For in vivo tests, the nanoprobes showed excellent tumor targeting ability, long blood circulation time, and could remarkably inhibit the growth of tumor. Our results will help to advance the design of combination strategies to enhance the efficacy of imaging-guided cancer therapy. Statement of Significance: The as-prepared CDGM NPs could accumulate into the tumor tissue with the enhanced permeability and retention (EPR) effect as well as the active tumor targeting ability from the MMP2 polypeptides. With the acid-sensitive linker, the doxorubicin (DOX) would be released from the synthesized nanoparticles after exposing to the acid tumor microenvironment. The CDGM NPs exhibit excellent tumor targeting ability and could remarkably suppress the growth of tumor compared with free Ce6 and DOX.